Emergency Cesarean Delivery in a Guillain- Barre Syndrome Patient - Rahman, Md Abdur; Hossain, Md Mozaffer; Mondal, Subrata Kumar; Islam, Atiqul; Shoman, Mohiuddin; Begum, Muslema; Bari, AKM Shamsul; Khanom, Mahmuda (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Guillain-Barré syndrome is an acute inflammatory demyelinating polyradiculopathy characterized by progressive motor weaknes, areflexia, and ascending paralysis. Guillain-Barré syndrome is extremely rare in pregnant patients, and there are no established guidelines for delivery or safest anesthetic methods. We report an emergency Cesarean delivery in the case of a 25-year old woman who was diagnosed as Guillain-Barré syndrome at her 26 weeks gestation. Tracheostomy was performed as prolonged ventilatory support was required in the intensive care unit. The respiratory difficulty was exacerbated by the growth of the fetus, necessitating emergency Cesarean delivery. The delivery was successfully performed under general anesthesia, and the patient recovered without neurological sequelae. Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 39-42